Relationship Between Self Esteem and Meaning In Life In Breast Cancer Patients At The Agricultural Regional Hospital of Jember Regency - Dewi, Erti Ikhtiarini; Salsabila, Miftah; Fitria, Yeni (Universitas Pendidikan Indonesia, 2024)
Introduction: Breast cancer is one of the most common non-communicable diseases in Indonesia. The impact that appears on breast cancer patients is a decrease in self-esteem which will influence the patient's difficulty in finding the meaning of life. Objectives: This study aims to determine the relationship between self-esteem and the meaning of life in breast cancer patients in hospitals in the agricultural region of Jember Regency. Methods: This research used quantitative research methods with a cross-sectional study approach. This research used a purposive sampling method involving 86 breast cancer patients. The research was conducted at the Baladhika Husada Level III Hospital in Jember. Data collection was carried out using the Rosenberg Self-Esteem Scale (RSES) questionnaire and the Meaning of Life Questionnaire (MLQ). Result: The results showed that the majority of breast cancer patients had high self-esteem (87.2%) and the majority of breast cancer patients had high meaning in life (76.7%). Data analysis using Kendall Tau-C showed (p-value = 0.004 with r value = 0,26), which means there is a relationship between self-esteem and the meaning of life for breast cancer patients. Conclusion: Breast cancer patients who have high self-esteem tend to be better and able to face life challenges, increase the patient's enthusiasm to achieve goals, and find meaning in their lives. This helps patients view their lives positively so that breast cancer patients are can accept and adapt to the disease and changes that occur in their lives.